2019
DOI: 10.1097/icb.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Toxicity After Inadvertent Intracameral Injection of High Dose of Cefuroxime During Cataract Surgery: A Case Series

Abstract: Anterior and posterior inflammation has been described after intracameral injection of high dose of cefuroxime. In this study, 10 mg to 12.5 mg of intracameral cefuroxime is shown to be, principally, toxic to the retina with transient or permanent retinal changes on optical coherence tomography which correlate with visual outcomes postoperatively. Protocols to avoid dilution errors should be available in theaters during cataract surgery where such commercial preparations are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 6 publications
0
22
1
4
Order By: Relevance
“… 25 However, ocular toxicity secondary to cefuroxime has been reported with standard 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 and higher doses (2–100mg) of ICC. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 A summary of published reports including the clinical features and management is presented in Table 1 . In cataract surgery, toxicity secondary to subconjunctival cefuroxime has also been reported and is thought to be due to the passage of the drug into the eye through corneal wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 However, ocular toxicity secondary to cefuroxime has been reported with standard 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 and higher doses (2–100mg) of ICC. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 A summary of published reports including the clinical features and management is presented in Table 1 . In cataract surgery, toxicity secondary to subconjunctival cefuroxime has also been reported and is thought to be due to the passage of the drug into the eye through corneal wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In cataract surgery, intracameral cefuroxime (ICC) became widely accepted, following a multicentre study by the European Society of Cataract and Refractive Surgeons (ESCRS) which demonstrated that ICC administration reduced the incidence of post-op endophthalmitis by five-fold. 1 However, there have been reports of ocular toxicity with standard (1mg/0.1mL) 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 and high doses (2–100mg) of ICC, 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 including retinal toxicity, corneal toxicity and uveitis, with a risk of permanent visual loss from retinal structural damage. 7 , 14 , 21…”
Section: Introductionmentioning
confidence: 99%
“…Intracameral vancomycin is associated with hemorrhagic occlusive retinal vasculitis (HORV) (48), and retinal toxicity is also associated with cefuroxime at high (49,50) and standard intracameral doses (51).…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…Эти проявления встречаются после однократного внутрикамерного или трансцилиарного введения стандартных, а в некоторых случаях избыточных доз гентамицина и цефуроксима и проявляются в виде неинфекционного панувеита, синдрома ретинальной ишемии, атрофии зрительного нерва, геморрагических нейроретиноваскулитов и др. [16][17][18]. Эти данные еще раз подтверждают необходимость прецизионного, строго дозированного использования антибиотиков в офтальмологии, особенно в тех случаях, когда речь идет о максимальном сохранении зрительных функций.…”
Section: актуальностьunclassified